2022
DOI: 10.1002/eat.23765
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID‐19 pandemic on intensive cognitive behavioral therapy outcomes in patients with anorexia nervosa—A cohort study

Abstract: Objective This study aimed to assess the impact of the COVID‐19 pandemic on the efficacy of an intensive treatment based on enhanced cognitive behavioral therapy (CBT‐E) in patients with anorexia nervosa. Methods This cohort study analyzed 57 patients with anorexia nervosa who experienced the COVID‐19 pandemic during intensive CBT‐E, comparing their outcomes (body mass index [BMI], eating‐disorder and general psychopathology, and clinical impairment) with those of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…This imperative is particularly pronounced when considering adolescents. Once again, our data accentuate the crucial importance of directing attention to the specific needs of youth in the ED field, encompassing their cognitive, emotional, and social requirements [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 77%
“…This imperative is particularly pronounced when considering adolescents. Once again, our data accentuate the crucial importance of directing attention to the specific needs of youth in the ED field, encompassing their cognitive, emotional, and social requirements [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 77%
“…Healthcare systems have been overwhelmed by the pandemic's effects on staff members and the increased support required by patients, showing the psychological burden of the exacerbation of ED symptomatology caused by the loss of in-person support, the feeling of being undeserving of help, and the limitations of online treatment options [12]. Moreover, evaluation of the changes in the effectiveness of treatment before and during the COVID-19 pandemic indicates a reduction in the improvement in patients, calling for evaluations on the possible necessity of specific strategies and procedures to help them [13]. Overall, this evidence showed the possible role of environmental adversity in developing psychological distress, understood as isolation, low mood, anxiety, lack of structure, disruption to routines, and media/social media messages around weight and exercise [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Both groups exhibited significant improvements in BMI, eating disorder and general psychopathology, and clinical impairment scores from baseline to the 20-week follow-up. However, the improvement was more pronounced in the pre-pandemic control group than those treated during the COVID-19 pandemic [8].…”
Section: Introductionmentioning
confidence: 82%
“…These differences could be attributed to different treatment settings and different groups of patients (adults vs. adolescents). Some prior research, including on patients treated via intensive CBT-E, has suggested a more pronounced improvement among patients treated before the COVID-19 pandemic [8]. However, this disparity may be attributable to differences in the sample assessed before the pandemic.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation